ANALISIS TEORI LABELLING DAN DEKONSTRUKSI TOKOH DALAM NOVEL BULAN TERBELAH DI LANGIT AMERIKA KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA - Devandra Eka Savitri; Elly Firdaus; Suwarsono Suwarsono (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2018)
The research focuses its attention on the role problem is the labeling theory. This theory assumes that in society as a social structure there are various deviations. Deconstruction is the ever-present waste between